Personal values Involved in choosing a College: Analysis Using the Means-End Chain Approach - Viana, Lílian Carolina; Silva, Cleiton Martins Duarte da; Vieira, Kelly Carvalho; Viana, Marcelo Ferreira; Vilas Boas, Luiz Henrique de Barros (Revista de Administração da UFSM, 2014)
The investigation the reasons for choice of products and services by consumers stands out as relevant in the area of ​​market studies, as well as notes management for any organization. Through the Theory of Means-End Chain proposed by Gutman (1982), which relates the "means" (attributes and benefits) linked to the consumption of products or services with the "ends" in terms of personal values ​​achieved, it is possible understand of the meanings that consumers attribute the choice of products and services in a more abstract level. Thus, the objective of this study is to understand what aspects, considering attributes, consequences and personal values ​​guide the behavior of students in choosing the nursing course at a private institution of higher education. Based on the theory mentioned it was adopted the technique laddering, in-depth interview and analysis methodology and representation of the hierarchical value map, which was interpreted and analyzed in order to understand the cognitive structure of students’ choice.The analysis of the results indicate that students are guided primarily by hedonistic values​​ of happiness itself the choice of nursing in college studied.